A novel thyroid cancer nodal map classification system to facilitate nodal localization and surgical management: The A to D map. (30th November 2016) - Cunnane, Marybeth; Kyriazidis, Natalia; Kamani, Dipti; Juliano, Amy F.; Kelly, Hillary R.; Curtin, Hugh D.; Barber, Samuel R.; Randolph, Gregory W.
Abstract : Objectives/Hypothesis: To evaluate the effectiveness, reproducibility, and usability of our proposed nodal nomenclature and classification system employed for several years in our high‐volume thyroid cancer unit, for the adequate localization and mapping of lymph nodes in thyroid cancer patients with extensive nodal disease. Study Design: Retrospective review. Methods: Thirty‐three thyroid cancer patients with extensive nodal disease treated from January 2004 to May 2013 were included in our study. Preoperative ultrasound and computed tomography scans of these patients were reanalyzed by blinded radiologists to investigate the feasibility for the assignment of abnormal lymph nodes to compartments defined in our proposed nodal classification system and to identify areas of difficulty in the assignment. Results: Analysis of nodal localization revealed a discrepancy in compartment agreement between the two radiologists in the assignment of abnormal nodes in nine patients (9/33, 27%). In six patients (6/33, 18%), discrepancy existed in labeling paratracheal and pretracheal nodes. In three patients (3/33, 9%), disagreement arose in the classification of retrocarotid nodes into lateral versus central compartment. A further refinement of the definition of key borderline regions of the pretracheal versus paratracheal and retrocarotid regions of our classification improved the agreement and demonstrated a complete concordance (100%) amongst the reviewing radiologists. Conclusions: The proposed nodal classification system, derived specifically for differentiated thyroid carcinoma, with readily identifiable anatomic boundaries on imaging and at surgery, facilitates communication among multidisciplinary physicians and aids in creating a uniform and reproducible radiographic nodal map to guide surgical therapy. Level of Evidence: 4 Laryngoscope, 127:2429–2436, 2017